Fighting for fares - Garnham, Alina,Stacey, Derek G. (Department of Economics, Queen's University, 2022)
In this paper, we study how the emergence of Uber in a large North American city affects the financial value of taxicab licenses. A taxicab license provides a claim to a stream of dividends in the form of rents generated by operating the taxicab or leasing the license. The introduction of Uber undoubtedly affects the anticipated stream of div- idends because Uber drivers capture part of the farebox revenue that might otherwise go to the owners/drivers of licensed taxicabs. At the same time, the launch of Uber's innovative technology-driven approach to the provision of ride-hailing services can be viewed as a partial obsolescence of the traditional taxicab approach. The economic incentives facing market participants may therefore change as Uber gains momentum in the ride-hailing market, which could further affect the market value of licensed taxi- cabs. Using transaction-level data, we apply a theory of asset pricing to the secondary market for Toronto taxicab licenses to explore these potential price effects. We learn that both the farebox and innovation effects contribute to the overall decline in market value, with the farebox effect accounting for just over half of the 170K price decline from 2011 to 2017. We explore the welfare implications for taxicab license owners with counterfactual simulations. We find that, consistent with the anti-Uber protests organized by Toronto taxi drivers, there was a high willingness to pay among license holders to prevent or postpone the launch of Uber's ridesharing services.
10419/281091
Keywords: Graue Literatur; Uber; Taxicabs; Asset Pricing; Search and Bargaining